A new method for approximate solutions of some nonlinear equations: Residual power series method - İnç, Mustafa; Korpinar, Zeliha S.; Al Qurashi, Maysaa' Mohamed; Baleanu, Dumitru (Sage Publications Ltd, 2016)
In this work, a powerful iterative method called residual power series method is introduced to obtain approximate solutions of nonlinear time-dependent generalized Fitzhugh-Nagumo equation with time-dependent coefficients and Sharma-Tasso-Olver equation subjected to certain initial conditions. The consequences show that this method is efficient and convenient, and can be applied to a large sort of problems. The approximate solutions are compared with the known exact solutions.
Keywords: Residual power series method; nonlinear time-dependent generalized Fitzhugh-Nagumo equation; Sharma-Tasso-Olver equation